Physical impact of bottom trawling on seafloor sediments in the German North Sea - Bruns, Ines; Bartholomä, Alexander; Menjua, Francine; Kopf, Achim (Frontiers in Earth Science, 2023)
Bottom trawling is a well-known global phenomenon and has significant physical impact on the seabed habitat, such as compression, displacement and mobilization of the sediment. Thus, it is necessary to examine how it alters the seabed e.g., in order to support strategies in marine spatial planning and nature conservation. Numerous studies aim at quantifying the physical impact of bottom trawling on the seabed based on laboratory experiments and/or modeling approaches but, to our knowledge, none of them include in-situ techniques. The North Sea is heavily influenced by bottom trawling and thus, we selected an area in the southern North Sea was selected where side scan sonar data identified areas showing the physical impact of bottom trawling by means of trawl marks. Here, we deployed the dynamic penetrometer Nimrod was deployed in order to determine the changes in sediment strength (quasi-static bearing capacity) compared to the reference sites (absent trawl marks). Our The results attest a higher penetration depth of Nimrod and a lower sediment strength in the trawled area compared to the un-trawled reference sites. This is likely related to an increase in water content and a decrease in bulk density of the sediment that was re-worked by bottom trawling. A spatial analysis of the quasi-static bearing capacities in the trawled area and the backscatter characteristics of the trawl marks suggest that the lowest sediment strength is rather obtained where a single bottom trawling took place recently. In contrast, regions with repeated trawling events in the past show elevated sediment strength.